Optimal operating strategy of ash deposit removal system to maximize boiler efficiency using CFD and a thermal transfer efficiency model - Park, Hyundo; Lee, Jesung; Lim, Jonghun; Cho, Hyungtae; Kim, Junghwan (Journal of industrial and engineering chemistry (Seoul, Korea), 2022)
Ash deposits generated during the combustion process on the outer tube surface of a boiler reduces the boiler’s efficiency. In most boilers, ash deposits are physically removed with high-pressure steam using an ash deposit removal system, sootblower. However, most sootblowers spray steam with excessive pressure, without considering the characteristics of the ash deposit, resulting in problems such as waste of steam energy and damage to equipment. In addition, an optimal operation strategy based on the position of the sootblower and the injection angle of the steam nozzle are not considered, leading to a lowered efficiency of ash deposit removal and steam waste. Hence, this study proposes a novel method to determine the optimal operating conditions of a sootblower using computational fluid dynamics (CFD) and a thermal transfer efficiency model considering the properties of the ash deposits. This method was developed based on a commercial recovery boiler, and consists of (i) a sootblowing steam velocity model that considers the ash deposit characteristics, (ii) a three-dimensional CFD model considering the interior design of the boiler, and (iii) a thermal transfer efficiency model that calculates the thermal resistance depending on the amount of ash deposit removed. Case studies were performed to calculate the amount of ash deposit removed for various ash deposit thicknesses, and sootblower positions and angles using this methodology. The boiler heat transfer efficiency was calculated using the calculated ash deposit removal amount and thermal transfer efficiency model, and the optimum operating conditions for the sootblower with the optimum heat transfer efficiency were derived. This study presents a guideline for efficiently operating sootblowers according to the ash deposit characteristics, and can be applied not only to recovery boilers but also to other boilers in which ash deposits are generated.